ANALISIS KESALAHAN FONOLOGI PADA FILM BAHASA SANTRI “INTHIQ RASMIYYATAN” DAN RELEVANSINYA TERHADAP PEMBELAJARAN BAHASA ARAB - Tria Lis Utami, Resgi Widati (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
This research aims to find out the various forms of phonological errors that occur in the Arabic language film entitled Inthiq Rasmiyyatan and the causes of these phonological errors. The research method used in this research is descriptive qualitative with data obtained from the conversations of the cast of the santri language film Inthiq Rasmiyyatan. This research uses data collection techniques in the form of listening and recording techniques. Then, the data that has been obtained is analyzed using the error analysis technique or correct analysis. The results of this study reveal that 3 types of phonological errors occur in the conversations of the cast of the film, including phoneme replacement, phoneme reduction, and phoneme addition. The phonological errors occur due to the presence of Arabic phonemes that are almost similar or the influence of first language acquisition. The results of this study can be used as a reference for teachers in conducting learning activities and for Arabic learners in learning and using the language. This is done so that teachers and learners of Arabic can pay more attention to the pattern of the release of language sounds in words, phrases, and clauses. Thus, teachers and learners can pronounce each phoneme correctly in speaking Arabic daily.